Pengelolaan Limbah Medis Rumah Sakit Gigi Mulut - Dwi Windu Kinanti; Retno Kusniati; Hilda Dwi Handayani (Universitas Muhammadiyah Semarang, 2021)
Background: Hospital environmental management is a series of cycles and management strategies to develop environmental management capacity. The hospital is one of the biggest waste producers that has the potential to cause pollution to the surrounding environment, both the community and the hospital itself. Hospitals produce waste that increases every day, especially solid waste which can be divided into medical and non-medical waste. Management of hospital medical and non-medical solid waste is needed for the comfort and cleanliness of the hospital environment, because it can prevent health problems. Method: This type of research is qualitative with a research design a Focus Group Discussion (FGD), with a sample of 5 respondents. The types of data used are primary and secondary data. Result: Based on results of the research, it was found that the Unimus Dental Hospital has a permit and also corporation with third parties related to medical management, where in this case, of course, the Unimus Dental Hospital already has a storage room for medical and non-medical waste according to applicable standards. Conclusion: Management of medical waste at RSGM Unimus is already good, it needs regular mentoring and evaluation so that performance in medical waste management is well monitored.